Census characteristics of Illinois sober living homes: A geographic information systems study. Issue 1 (2nd January 2021) - Callahan, Sarah; Hwang, Sungsoon; Isler, Brandon; Wiedbusch, Elzbieta; Jason, Leonard A.
Abstract: Recovery homes currently provide a supportive, cohesive setting following addiction treatment to thousands of individuals who often have the least resources and consequently a high risk of relapse. Such homes are particularly important regarding reducing inequality, particularly for those with substance use disorders exiting inpatient treatment or jail/prison, and many of these individuals have experienced homelessness and high rates of psychiatric co-morbidity. Yet, the success of these houses and their residents is likely related to the ability of the residents to obtain employment. This study geocoded data from 52 Oxford House recovery homes throughout Illinois. Data indicated that Oxford Houses in Illinois were often located in areas with the highest unemployment activity in the state. Placing homes in communities with higher job opportunities and employment rates could increase employment for individual residents and, subsequently, reduce inequality by increasing their odds of long term abstinence.